Interação entre a dinâmica urbana e a eficiência da Estação de Tratamento de Esgoto de Boa Vista Roraima de 2012 a 2022 - Rodriguez, Lilitza Eugenia Trías (2024)
The municipality of Boa Vista, RR has a Sewage Treatment Plant (STP), which is a set of facilities and equipment designed to purify the sewage produced. The Boa Vista STP is a stabilization pond type, consisting of two optional ponds and two maturation ponds, which aims to care for and preserve natural resources such as water and soil, while also protecting the health of the population through sanitary works. For this reason, this research sought to evaluate the performance of the STP regarding its efficiency between the years 2012 to 2022, through the parameters biochemical oxygen demand, chemical oxygen demand, suspended solids and thermotolerant coliforms, in the influent and effluent of each pond. On the other hand, the relationship between urban dynamics and the efficiency of the STP was analyzed through cartographic information, bibliographic material and secondary data from the Brazilian Institute of Geography and Statistics - IBGE (in situ visit to the Boa Vista headquarters). The data used for water quality parameters at the ETE are secondary, provided by the Municipal Basic Sanitation Plan - PMSB and the Roraima Water and Sewage Company - CAER, and were treated with descriptive statistics, analyzed, and compared with the values established by Resolutions No. 357/2005, 430/2011, and 034/2012. The results and conclusions show that the ETE is not operating efficiently due to the high trend of the parameters COD (mg/L), SS (mg/L), and TC (NMP/100 mL), and failure to comply with the maximum permissible limit established by Resolutions No. 034/2012 and 357/2005, possibly due to the discharge of sewage from septic tank cleaning trucks with high concentrations of these parameters. The performance of the anaerobic, facultative and maturation lagoons for the period 2012 to 2022 showed little or no removal efficiency in the study parameters. On the other hand, the installation of the ETE influenced the urban dynamics of the city in a positive way, by purifying the sewage generated by the population, protecting the health of the inhabitants and natural resources, as long as its operation is efficient and complies with environmental legislation. The ETE adapted to urban and population demand with the 2013 renovation, connecting new connections to the sewage network. In terms of negative impact, the performance problem leads to the possible pollution of the waters of the Branco River (receiving body of water), generating bad odors that would bother the population. It is recommended that the competent agencies carry out more detailed and rigorous monitoring of the quality of the water in the tributary and effluent of each lagoon, in order to guarantee the operational efficiency of the ETE and compliance with the laws in this area.